Mucus retention cyst of the maxillary sinus: the endoscopic approach - T. Hadar, J. Shvero, B. I. Nageris, E. Yaniv (Blackwell Synergy, 2000)
Benign mucosal cyst of the maxillary sinus results from the accumulation of mucus within the soft tissue that lines the sinuses as a result of obstruction of a duct or gland within the epithelial layer. The reported incidence is 1.4–9.6%,1–5 and it is usually discovered incidentally on plain radiograph or computed tomogram (CT) of the sinuses or on panoramic radiography. 1,3,6 Radiographically, the cyst is a rounded, dome-shaped, soft tissue mass, most commonly situated on the floor of the maxillary sinus; it often contains clear, yellowish fluid.